Potenciais hídricos no solo sobre a eficácia de herbicidas em cenchrus echinatus L - Klar, Antonio Evaldo [UNESP]; Pereira, Maria Renata Rocha; Martins, Dagoberto [UNESP] (My University, 2015)
This study aimed at relating the efficiency of ACCase-inhibiting herbicides applied to post-emergence Cenchrus echinatus plants with three different herbicide applications (fluazifop-p-butyl, haloxyfop-methyl and sethoxydim + Assist mineral oil). The plants were under different water levels in the soil, and the experiment was conducted in a greenhouse using a completely randomized experimental design with four replicates and a 3 x 4 factorial design with three minimum soil water potential (Ψ = -0.03; -0.07 and -1.5 MPa) and four doses of the products (100, 50, 25 and 0% recommended dose). Herbicide application was performed at the 4-6-leaf vegetative stage and water management was initiated at the 2 leaf-development stage. Water was replaced when the soil reached minimum Ψ of -0.01 MPa for the three levels mentioned. Visual evaluations of phytotoxicity were performed weekly from 7 to 28 days after application and, thereafter, the evaluation of plant dry matter. The efficiency of control of the different herbicides was affected by water management, being lower in plants grown in minimum soil water potential of -1.5 MPa for all study herbicides.
Water potential in the soil on the effectiveness of herbicides in cenchrus echinatus L
Keywords: Chemical control; Sandbur; Water restriction; Weed